KEAJAIBAN CIPTAAN DAN IMPLIKASINYA DALAM PEMBELAJARAN - Nangsari Ahmad (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2012)
Man presented on this earth - to borrow a term in computer science - with a hardware and software. The brain is the hardware and the software is reasonable. According recognized expert neuroscience (neuroscience) has 100 biliun brain nerve cells (neurons), and each cell can make 20,000 relationships. Relationships that determine a person's potential. In addition, human beings are endowed almighty with a software, the reason (thought). The reason to process data from the five senses (data entry of hearing, sight, smell, taste, touch or sense) to mind that are stored in the brain as a